Distinct host preconditioning regimens differentially impact the antitumor potency of adoptively transferred Th17 cells - Gregory B Lesinski; Chrystal M Paulos; Hannah M Knochelmann; Megan M Wyatt; Guillermo O Rangel Rivera; Anna C Cole; Megen C Wittling (Journal for ImmunoTherapy of Cancer)
Background How distinct methods of host preconditioning impact the efficacy of adoptively transferred antitumor T helper cells is unknown.Methods CD4+ T cells with a transgenic T-cell receptor that recognize tyrosinase-related peptide (TRP)-1 melanoma antigen were polarized to the T helper 17 (Th17) phenotype and then transferred into melanoma-bearing mice preconditioned with either total body irradiation or chemotherapy.Results We found that preconditioning mice with a non-myeloablative dose of total body irradiation (TBI of 5 Gy) was more effective than using an equivalently dosed non-myeloablative chemotherapy (cyclophosphamide (CTX) of 200 mg/kg) at augmenting therapeutic activity of antitumor TRP-1 Th17 cells. Antitumor Th17 cells engrafted better following preconditioning with TBI and regressed large established melanoma in all animals. Conversely, only half of mice survived long-term when preconditioned with CTX and infused with anti-melanoma Th17 cells. Interleukin (IL)-17 and interferon-γ, produced by the infused Th17 cells, were detected in animals given either TBI or CTX preconditioning. Interestingly, inflammatory cytokines (granulocyte colony stimulating factor, IL-6, monocyte chemoattractant protein-1, IL-5, and keratinocyte chemoattractant) were significantly elevated in the serum of mice preconditioned with TBI versus CTX after Th17 therapy. The addition of fludarabine (FLU, 200 mg/kg) to CTX (200 mg/kg) improved the antitumor response to the same degree mediated by TBI, whereas FLU alone with Th17 therapy was ineffective.Conclusions Our results indicate, for the first time, that the antitumor response, persistence, and cytokine profiles resulting from Th17 therapy are impacted by the specific regimen of host preconditioning. This work is important for understanding mechanisms that promote long-lived responses by adoptive cellular therapy, particularly as CD4+ based T-cell therapies are now emerging in the clinic.